ANALISIS EFISIENSI USAHATANI TEBU PETANI MITRA DAN NON MITRA DI KABUPATEN BLORA JAWA TENGAH - Yahdi Zaky; Rachmat Pambudy; Harianto Harianto (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2019)
Sugarcane is one of the commodities in the plantation sector which is a mainstay in an effort to increase the welfare of farmers. Blora Regency is one of the regencies which is the center of sugarcane production in Central Java Province with the lowest production. The research objectives are (1) to analyze the factors that influence sugarcane production in Blora Regency; (2) analyzing the technical efficiency of sugarcane farming; (3) analyzing the income level of sugarcane farmers. Sampling was used by random and snowball sampling method to collect 80 sugarcane farmers. The collected data is then analyzed using Cobb-Douglas stochastic frontier production function, farm income analysis and different test analysis (t-analysis).The results showed that the variables of urea fertilizer, za, phonska and organic fertilizer had a significant effect on sugarcane farming production in Blora Regency. Technical efficiency level of sugarcane farming, partners and non-partners are efficient with an average of technical efficiency is 0,89. The lengthy farming variable becomes the only inefficiency estimator variable that has a significant effect on sugarcane farming. Based on the income analysis, sugarcane farmers who done farming activities through a partner pattern have a greater income of Rp. 8.408.180 with a R / C ratio 1,236. While non-partner pattern income is Rp. 2.438.317 with a R / C ratio of 1,071 and Rp. 460.510 with a R / C ratio of 1,013. Based on the results of this research, it is important to choose partner pattern on sugarcane farming in Blora Regency.